2010
DOI: 10.1039/b923147a
|View full text |Cite
|
Sign up to set email alerts
|

Peptide modified nanocarriers for selective targeting of bombesin receptors

Abstract: The present work describes new supramolecular aggregates obtained by co-assembling two different amphiphilic molecules, one containing the bioactive bombesin peptide (BN), or a scramble sequence, and the other, the DOTA chelating agent, (C18)(2)DOTA, capable of forming stable complexes with the radioactive (111)In(III) isotope. The peptide in the amphiphilic monomer is spaced by the lipophilic moiety through ethoxylic spacers of different length: a shorter spacer with five units of dioxoethylene moieties in (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…Although tumor uptake values of the M21 tumors were slightly higher than those of the negative control M21-L tumors (with lowest values for lowRLP), the differences were not significant. This outcome was not as anticipated since the in vitro behavior of RLPs seemed to be promising and the authors' group has already demonstrated a specific tumor binding of 2.5% ID/g with tyrosine-3-octreotide liposomes, 22 which is comparable to the data of Accardo et al 45 An even better tumor uptake of 5.2% ID/g in mice bearing a somatostatin receptor-2-positive human neuroendocrine tumor was found for copper-64-labeled octreotate-encapsulated liposomes. 25 Reasons for the reduced tumor targeting of RLPs might be related to the PEG(2000) chain length as reported by Herringson and Altin.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Although tumor uptake values of the M21 tumors were slightly higher than those of the negative control M21-L tumors (with lowest values for lowRLP), the differences were not significant. This outcome was not as anticipated since the in vitro behavior of RLPs seemed to be promising and the authors' group has already demonstrated a specific tumor binding of 2.5% ID/g with tyrosine-3-octreotide liposomes, 22 which is comparable to the data of Accardo et al 45 An even better tumor uptake of 5.2% ID/g in mice bearing a somatostatin receptor-2-positive human neuroendocrine tumor was found for copper-64-labeled octreotate-encapsulated liposomes. 25 Reasons for the reduced tumor targeting of RLPs might be related to the PEG(2000) chain length as reported by Herringson and Altin.…”
Section: Discussionsupporting
confidence: 74%
“…The major uptake was in the spleen and liver, with the highest liver uptake values of 45 In-highRLP: 10.0% ± 4.7% ID/g). Uptake values for the other tissues (heart, stomach, pancreas, intestine, kidneys) at 1 hour postinjection were rather low (,9.0% ID/g), with the exception of lungs where the accumulation was 13.1% ± 1.9% ID/g for 111 In-lowRLP, 14.9% ± 4.1% ID/g for 111 In-medRLP, and somewhat lower for highRLP (7.1% ± 3.2% ID/g) (Figure 4).…”
Section: Evaluation Of Rlps In Vivomentioning
confidence: 99%
“…[31][32][33] In-vitro and in-vivo experiments, carried out on radiolabeled liposomes containing the BN (7)(8)(9)(10)(11)(12)(13)(14) peptide fragment, demonstrate that the peptide, exposed on the liposome surface, maintains the capability to selectively target aggregates to GRPR-expressing xenografts. 27 This paper describes new BN-conjugated nanosystems for theranostic purposes with improved properties, both in the synthesis and formulation aspects and for their in-vitro and in-vivo behavior. These liposomes are based on the coaggregation of 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC) phospholipid with a new synthetic amphiphilic monomer, MonY-BN (Figure 1), containing in the same molecules the BN (7)(8)(9)(10)(11)(12)(13)(14) peptide fragment, the DTPA chelating agent, the hydrophobic moiety with two C18 alkyl chains, and polyethylene glycol (PEG) spacers.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Interesting results have been obtained by using the BN peptide. 27 The 14-residue BN peptide, its eight-residue C-terminal peptide sequence (BN [7][8][9][10][11][12][13][14]), or other BN analogues acting as antagonists may be used to target BN receptor subtype 2, also known as gastrin releasing peptide receptor (GRPR). GRP receptors have been found overexpressed in cell lines derived from several human tumor types (ovarian cancer, breast cancer, and prostate cancer).…”
Section: Introductionmentioning
confidence: 99%
“…98 They were obtained by the combination of two amphiphilic synthetic monomers: a first, more abundant, monomer based on a lysine residue carrying a DOTA chelating agent on the epsilon amino function and an hydrophobic moiety with two C18 chains on the alpha amino function; and a second monomer containing the same hydrophobic moiety, PEG spacers, and the 7-14 BN peptide fragment. The DOTA containing monomer drives to form stable liposomes in water solution independently from the presence of 10% in peptide monomer, as demonstrated by SANS (small angle neutron scattering) and DLS (dynamic light scattering) techniques.…”
Section: Liposomes and Micellesmentioning
confidence: 99%